TECHNOLOGICAL INNOVATIONS AS A GROWTH STRATEGY: AN ANALYTICAL OF THE PRIVATE BANKING SECTOR - Krishna, J. S. Mohana; Maheshwari, R. Uma (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Advanced technologies are increasingly taking over roles traditionally held by bank employees. The fast-evolving landscape of the banking industry, along with the ongoing challenges it presents, necessitates a continuous enhancement of knowledge and skills within organizations. Embracing new technology is crucial for achieving economies of scale and improving efficiency and effectiveness compared to existing systems. Innovations driven by technology will play a vital role in providing diverse and tailored banking services to a wide range of customers at lower costs. Key technological advancements include Internet banking, mobile banking, automated teller machines, and investments in software solutions. The banking sector is pivotal in accelerating socio-economic development, particularly in developing nations, where banks significantly contribute to economic growth through investments across various sectors. To maximize the benefits of these innovations, it is essential to create a system that promotes efficient investment in technology while minimizing the gap between revenue and costs associated with technological upgrades. A total of 280 participants from different private sector banks were surveyed using a stratified random sampling method, with a structured questionnaire designed to assess the impact and aspects of technological innovations in these banks.